Environmental and economic impacts of wave energy: Some public policy recommendations for implementation in Turkey - (:unkn) unknown (IGI Global, 2016)
The wave energy is one of the most important renewable energy sources and it has many advantages compared to other renewable energies. First, it is more reliable. Second, the cost of wave energy is competitive with other sources when it is used as a primary power source. Third, its energy density and deployment potential are higher than the wind and solar energy. Fourth, the wave energy has minor negative environmental impacts and production amount of the wave energy is more predictable. In the study, the applications of wave energy production are discussed in European Union countries in which have started to operate wave energy, recently. It is also tried to evaluate the feasibility of wave energy production opportunities in Turkey. As a result of the study, it can be said that the Black Sea has the highest wave energy potential in Turkey. Industrial production of wave energy actualized by fiscal incentives and this may lead to many social benefits such as increasing employment, reducing external dependency and diminishing greenhouse gases emission. © 2016 by IGI Global. All rights reserved.